2022
DOI: 10.3389/fpubh.2022.939053
|View full text |Cite
|
Sign up to set email alerts
|

Publication trends of research on COVID-19 and host immune response: A bibliometric analysis

Abstract: IntroductionAs the first bibliometric analysis of COVID-19 and immune responses, this study will provide a comprehensive overview of the latest research advances. We attempt to summarize the scientific productivity and cooperation across countries and institutions using the bibliometric methodology. Meanwhile, using clustering analysis of keywords, we revealed the evolution of research hotspots and predicted future research focuses, thereby providing valuable information for the follow-up studies.MethodsWe sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…The USA, England, and China ranked the top three countries/regions in accordance with the number of publications, which meant that these three countries/regions represented the highest level in COVID-19 vaccine research worldwide. Among that, more than half of the articles (56%) had participation from American scholars, because basic research conditions in the USA are superior to other countries, with advanced laboratory equipment, adequate funding for scientific research, and first-class research teams [ 18 ]. Although China ranked third in the number of publications, the centrality value was zero (Table 2 ), indicating that China should strengthen international cooperation and carry out more in-depth research on COVID-19 vaccine research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The USA, England, and China ranked the top three countries/regions in accordance with the number of publications, which meant that these three countries/regions represented the highest level in COVID-19 vaccine research worldwide. Among that, more than half of the articles (56%) had participation from American scholars, because basic research conditions in the USA are superior to other countries, with advanced laboratory equipment, adequate funding for scientific research, and first-class research teams [ 18 ]. Although China ranked third in the number of publications, the centrality value was zero (Table 2 ), indicating that China should strengthen international cooperation and carry out more in-depth research on COVID-19 vaccine research.…”
Section: Discussionmentioning
confidence: 99%
“…Web of Science (WOS) represents a comprehensive, multidisciplinary database, which contains more than 12,000 authoritative and high-impact academic journals [ 17 ].What is more, it can provide critical information of all publications, including authors, authors’ affiliated institution, keywords, the number of citations, and publishers, etc. With its powerful functions and citation reports, it can quickly target highly impactful and representative researches, thus track down the research interests concerned to domestic and international authorities, as well as capture the growing trends of the discipline [ 18 ]. Hence, WOS database has been used extensively in bibliometric analysis [ 4 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Consultation with the literature on IPF revealed that several revisions of the diagnostic criteria and treatment principles of IPF were jointly published by scholars from the United States and Europe [ 15 , 32 , 35 ], indicating that the United States and Europe have given more attention to this field compared with other countries. Moreover, the United States has a considerable advantage in immune research, which is supported by the number of articles and is likely related to comprehensive national strength, professional researchers, sufficient research funds, and extensive international cooperation [ 23 , 29 , 30 ]. Thus, the United States is at the leading level in this field due to several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometrics is also used to evaluate the research contributions and collaborative relationships in a specific area across countries, institutions, journals, scholars, and articles [25], which can guide scholars to choose appropriate journals to publish their research results by analyzing citations and publication patterns [26][27][28]. More importantly, bibliometrics can also be used as a scientific basis for developing and implementing disease treatment guidelines [29].…”
Section: Introductionmentioning
confidence: 99%
“…The bibliometric analysis provides an excellent solution to systematically and quantitatively analyze large-scale publications, presenting the development history and scientific status. 18 It has been employed in various primary care and public health fields, including COVID-19, 19 chronic postsurgical pain, 20 rheumatoid arthritis, 21 and central sensitization. 22 Whereas bibliometric analysis in the field of dysmenorrhea is scarce.…”
Section: Introductionmentioning
confidence: 99%